Benzene sulfonate additive and application thereof in sodium-ion battery electrolyte
By using benzenesulfonate additives in sodium ion battery electrolytes, a stable inorganic SEI film is formed, which solves the problems of easy gas production, poor high and low temperature performance and short cycle life of existing electrolyte additives during circulation, and achieves high performance and long life of sodium ion batteries.
Patent Information
- Application Number
- CN202411831321.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-12
AI Technical Summary
The existing sodium ion battery electrolyte additives have limited improvements in battery performance, and there are problems such as easy gas production during circulation, poor high and low temperature performance, and short cycle life.
A benzene sulfonate electrolyte additive is designed, which contains phenyl groups and sulfonate groups, which can form a stable inorganic SEI film in the sodium ion battery electrolyte, and improve the battery's anti-overcharge performance and oxidation stability.
It effectively improves the high voltage resistance, working temperature range, safety and cycle stability of sodium ion batteries, extends the cycle life of the battery, and reduces production costs.
Smart Images

Figure CN119708043A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of battery electrolyte additives, in particular to a benzene sulfonate additive and application thereof in sodium ion battery electrolytes. Background Art
[0002] Since its commercialization, lithium-ion batteries have been widely used in electronic products, electronic communications, military aerospace, and electric vehicles. However, due to the low reserves and uneven distribution of lithium resources, the cost of using lithium mines is high, which in turn limits the development of the new energy industry. In contrast, sodium is abundant in the earth's crust and is evenly distributed. Therefore, the development of sodium-ion batteries as energy storage devices has the characteristics of low cost and good sustainability. Lithium and sodium elements belong to the same main group elements and have similar physical and chemical properties. In addition, sodium-ion batteries and lithium-ion batteries have similar working principles, and the battery production processes are highly similar. Therefore, the development of high-performance sodium-ion batteries has good application prospects, and is expected to replace some application scenarios of lead-acid batteries and lithium-ion batteries in the future, thereby supporting the sustainable development of large-scale energy storage technology.
[0003] The positive and negative electrode materials of sodium-ion batteries have been widely developed and explored, and the capacity of their electrode materials is comparable to that of lithium-ion batteries, but the matching electrolyte system is still under exploration. The electrolyte of sodium-ion batteries can be effectively improved by optimizing sodium salts, optimizing solvents, and introducing functional additives. However, the types of sodium salts are limited, the room for improvement is limited, and the cost is high; while the optimization of new solvents has a long development cycle, large investment, high production cost, and low cost performance; while the introduction of functional additives not only reduces the amount used, but also significantly improves the performance, and has the advantages of low cost and good economy. Therefore, the development of new electrolyte additives is of great significance to the development of sodium-ion batteries.
[0004] At present, reported electrolyte additives for sodium-ion batteries include vinyl sulfite (ES), succinonitrile (SN), vinyl carbonate (VC), etc. However, this series of electrolyte additives has limited improvement on the performance of sodium-ion batteries, and there are problems such as easy gas production during the cycle, poor high and low temperature performance, and short cycle life. Therefore, by designing appropriate additive molecules, they can be preferentially decomposed to form a uniform and stable SEI film, thereby greatly improving the electrochemical performance of sodium-ion batteries. Studies have shown that the introduction of aromatic ring groups into the electrolyte can effectively inhibit overcharge; sulfonate groups can increase the ionic conductivity of the electrolyte, which is conducive to the construction of a low-impedance SEI film, thereby achieving high rate performance and long cycle stability. However, the use of multiple additives together may lead to incompatibility, further affecting the performance of the battery.
[0005] In response to the above problems, it is urgent to design a benzenesulfonate electrolyte additive to improve the properties of sodium-ion battery electrolytes, so as to achieve the construction of sodium-ion batteries with a wide temperature range, long life and high rate. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a benzenesulfonate additive and its application in sodium ion battery electrolyte.
[0007] To achieve the above object, the present invention is implemented according to the following technical solutions:
[0008] One of the purposes of the present invention is to provide a benzenesulfonate additive, which is a compound of the structural formula shown in formula (I):
[0009]
[0010] Where: R 1 , R 2 , R 3 , R 4 and R 5 It is a hydrogen atom, a fluorine atom, a fluorinated alkane or a fluorinated ether group having 1 to 3 carbon atoms;
[0011] R 6 It is one of an alkane, a fluorinated alkane, a cyanated alkane and a silane group having 1 to 5 carbon atoms.
[0012] Furthermore, R 1 , R 2 , R 3 , R 4 and R 5 One of the following groups:
[0013]
[0014] R 6 One of the following groups:
[0015]
[0016] Preferably, the benzenesulfonate additive is one of the following compounds 1 to 52:
[0017]
[0018]
[0019] A second object of the present invention is to provide a use of a benzenesulfonate additive in a sodium ion battery electrolyte.
[0020] Specifically, a benzene sulfonate additive with a volume fraction of 0.1% to 10% is added to the sodium ion battery electrolyte.
[0021] Compared with the prior art, the phenyl group in the benzene sulfonate electrolyte additive of the present invention can improve the anti-overcharge performance of the battery, and the sulfonate group can form a stable inorganic SEI film and improve the oxidation stability. When it is used as an additive in the sodium ion battery electrolyte, it can not only effectively improve the battery's high voltage resistance, operating temperature range, safety, and cycle stability, but also be conducive to the promotion and application of low-cost, high-safety and long-cycle sodium ion secondary batteries in the field of energy storage, and solve the many performance shortcomings of the existing sodium ion secondary battery electrolyte; the synthesis method of the phenyl sulfonate molecule of the present invention is simple, the operation is safe, and the product purity is high. At the same time, it has excellent performance in sodium ion secondary batteries and is suitable for wide application. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The electrochemical performance diagram of NFPP||Na battery in EDF and EDFM electrolytes at room temperature;
[0023] Figure 2 The electrochemical performance diagram of NFPP||Na battery in Baseline and BEN electrolyte at 55℃;
[0024] Figure 3 The long cycle performance diagram of NFPP||Na battery in ED and EDM electrolytes at -20℃;
[0025] Figure 4 The rate performance diagram of NFPP||Na battery in PF and PFM electrolytes at room temperature;
[0026] Figure 5 The long cycle performance diagram of NFPP||Na battery in NPF and NPFM electrolytes at room temperature and high rate;
[0027] Figure 6 This is the long cycle performance diagram of NFPP||HC battery in TEMS electrolyte.
[0028] Above Figure 1-Figure 6 The symbols “△” and “○” in the chart represent the coulombic efficiency of the battery, and the symbols “▲” and “●” represent the capacity of the battery. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The specific embodiments described herein are only used to explain the present invention and are not used to limit the invention.
[0030] Unless otherwise specified, the raw materials and reagents used in the following examples are all commercially available; and the following examples take several typical compounds as sulfonamide / ester electrolyte additives.
[0031] Example 1
[0032] At 0°C, trimethylsilyl chloride (TMSCl) was slowly added dropwise to a tetrahydrofuran (THF) solution of 4-fluoromethylbenzenesulfonic acid, and the reaction was carried out for 4-6 hours. After the reaction was completed, the THF solvent was removed by rotary evaporation to obtain a crude reaction product, which was purified by reduced pressure distillation and recrystallization to finally obtain a high-purity compound 1;
[0033] The reaction formula is as follows:
[0034]
[0035] Example 2
[0036] At 0°C, trimethylsilyl chloride (TMSCl) was slowly added dropwise to a tetrahydrofuran (THF) solution of benzenesulfonic acid for 4-6 hours. After the reaction was completed, the THF solvent was removed by rotary evaporation to obtain a crude product. The crude product was purified by reduced pressure distillation and recrystallization to finally obtain a high-purity compound 9.
[0037] The reaction formula is as follows:
[0038]
[0039] Example 3
[0040] At 0°C, fluoroacetonitrile was slowly added dropwise to a tetrahydrofuran (THF) solution of benzenesulfonic acid for 4-6 hours. After the reaction was completed, the THF solvent was removed by rotary evaporation to obtain a crude product. The crude product was purified by vacuum distillation and recrystallization to finally obtain a high-purity compound 19.
[0041] The reaction formula is as follows:
[0042]
[0043] Example 4
[0044] At 0°C, trifluoromethanol was slowly added dropwise to a tetrahydrofuran (THF) solution of benzenesulfonic acid for 4-6 hours. After the reaction was completed, the THF solvent was removed by rotary evaporation to obtain a crude product. The crude product was purified by reduced pressure distillation and recrystallization to finally obtain a high-purity compound 28.
[0045] The reaction formula is as follows:
[0046]
[0047] Example 5
[0048] At 0°C, trifluoroethanol was slowly added dropwise to a tetrahydrofuran (THF) solution of 4-trifluoromethylbenzenesulfonic acid for 4-6 hours. After the reaction was completed, the THF solvent was removed by rotary evaporation to obtain a crude product. The crude product was purified by vacuum distillation and recrystallization to obtain a high-purity compound 35.
[0049] The reaction formula is as follows:
[0050]
[0051] Test Case
[0052] Exemplarily, the high-purity compound 1, high-purity compound 9, high-purity compound 19, high-purity compound 28 and high-purity compound 35 prepared in Examples 1 to 5 are used to prepare the corresponding sodium ion battery electrolytes:
[0053] Electrolyte containing high-purity compound 1
[0054] 1) In a glove box at 25°C with water and oxygen contents below 0.01 ppm, weigh 0.168 g of sodium hexafluorophosphate and dissolve it in 1 mL of a solution of ethylene carbonate, diethyl carbonate, and fluoroethylene carbonate (2:2:1 by vol.) and stir overnight to fully dissolve it to prepare a 1 mol L -1 The basic electrolyte of sodium ion battery (denoted as EDF).
[0055] 2) At 25°C, in a glove box with a water content and an oxygen content both lower than 0.01 ppm, 20 μL of compound 1 was mixed evenly with 1 mL of 1 mol / L sodium ion battery electrolyte (EDF), and the electrolyte was recorded as EDFM.
[0056] Electrolyte containing high-purity compound 9
[0057] 1) At 25°C, in a glove box with a water content and an oxygen content both lower than 0.01 ppm, 0.168 g of sodium hexafluorophosphate was weighed and dissolved in 1 mL of a solution of ethylene carbonate, propylene carbonate, diethyl carbonate, and fluoroethylene carbonate (6:6:6:1 by vol.), and stirred overnight to fully dissolve the solution to prepare a sodium ion battery electrolyte with a concentration of 1 mol / L (denoted as Baseline).
[0058] 2) In a glove box at 25°C with water content and oxygen content both below 0.01 ppm, 10 μL of compound 9 was mixed evenly with 1 mL of 1 mol / L sodium ion battery electrolyte (Baseline), and the electrolyte was recorded as BEN.
[0059] Electrolyte containing high-purity compound 19
[0060] 1) At 25°C, in a glove box with a water content and an oxygen content both lower than 0.01 ppm, 0.168 g of sodium hexafluorophosphate was weighed and dissolved in 1 mL of a solution of propylene carbonate and fluoroethylene carbonate (19:1 by volume), and stirred overnight to allow the solution to fully dissolve, thereby obtaining a sodium ion battery electrolyte (denoted as ED) with a concentration of 1 mol / L.
[0061] 2) At 25°C, in a glove box with a water content and an oxygen content both below 0.01 ppm, 10 μL of compound 19 was mixed evenly with 1 mL of 1 mol / L sodium ion battery electrolyte (Baseline), and the electrolyte was recorded as EDM.
[0062] Electrolyte containing high-purity compound 28
[0063] 1) In a glove box at 25°C with water and oxygen contents below 0.01 ppm, weigh 0.1224 g of sodium perchlorate and dissolve it in 1 mL of a solution of propylene carbonate and fluoroethylene carbonate (9:1 by vol.) and stir overnight to fully dissolve and mix well to prepare a 1 mol L -1 Sodium ion battery electrolyte (denoted as PF).
[0064] 2) At 25°C, in a glove box with a water content and an oxygen content both below 0.01 ppm, 5 μL of compound 28 was mixed evenly with 1 mL of 1 mol / L sodium ion battery electrolyte (PF), and the electrolyte was recorded as PFM.
[0065] Electrolyte containing high-purity compound 35
[0066] 1) At 25°C, in a glove box with a water content and an oxygen content both lower than 0.01 ppm, 0.1224 g of sodium perchlorate was weighed and dissolved in 1 mL of a solution of propylene carbonate and fluoroethylene carbonate (19:1 by volume), and stirred overnight to fully dissolve and mix evenly to prepare a sodium ion battery electrolyte (denoted as NPF) with a concentration of 1 mol / L.
[0067] 2) At 25°C, in a glove box with a water content and an oxygen content both below 0.01 ppm, 20 μL of compound 35 was mixed evenly with 1 mL of 1 mol / L sodium ion battery electrolyte (NPF), and the electrolyte was recorded as NPFM.
[0068] Preparation of NFPP electrode: Sodium iron pyrophosphate (NFPP), a polyanion cathode material, was used as the cathode material. NFPP, acetylene black, and PVDF binder were mixed at a mass ratio of 8:1:1, dispersed into slurry by N-methylpyrrolidone (NMP), and then transferred to a vacuum degassing machine. After stirring, a uniform slurry was obtained, which was evenly coated on aluminum foil with a 100 μm scraper, and then vacuum dried at 80 ° C for 12 h. The aluminum foil coated with the material was cut into electrode sheets with a diameter of 12 mm using a sheet cutter and stored in a glove box;
[0069] Preparation of hard carbon (HC) electrode: HC, SuperP and PVDF binder are dispersed into slurry by NMP in a mass ratio of 8:1:1. After stirring, a uniform slurry is obtained. The slurry is evenly coated on aluminum foil with a 50μm scraper, and then vacuum dried at 80°C for 12h. The electrode is cut into electrode sheets with a diameter of 12mm and stored in a glove box.
[0070] In the glove box, the prepared NFPP electrode sheet was used as the positive electrode; the HC electrode sheet and the sodium sheet with a diameter of 14 mm were used as the negative electrode; the glass fiber was used as the separator; the EDFM, BEN, DEM, PFM, NPFM and EMS electrolytes prepared by using sodium electrolytes (EDF, Baseline, ED, PF and NPF) and high-purity compounds 1, 9, 19, 28 and 35 as electrolyte additives were used to assemble NFPP||Na, HC||Na batteries and NFPP||HC sodium ion soft pack batteries. The test data were obtained using the electrochemical test system at -20℃~55℃.
[0071] The electrochemical performance of the prepared battery was tested. NFPP was used as the positive electrode, HC and sodium metal were used as the negative electrode, and NFPP||Na and NFPP||HC batteries were assembled with different electrolyte systems in different temperature ranges (-20℃~55℃), and their rate performance and cycle stability were tested.
[0072] At 25℃, 4V high voltage and 5C discharge rate, NFPP||Na battery was assembled using EDF and EDFM electrolytes, and the specific capacity and coulombic efficiency of the battery were tested. The results are as follows: Figure 1 As shown in (a) of Figure 1 (b) and (c) show the charge and discharge curves of NFPP||Na batteries assembled with two electrolyte systems.
[0073] from Figure 1 (a) and Figure 1 As can be seen from (b) in the figure, the NFPP||Na battery using the basic electrolyte (EDF) was overcharged after 1077 cycles, causing the battery to short-circuit. Figure 1 (a) and Figure 1 As can be seen from (c) in the figure, the EDFM electrolyte with compound 1 added to the basic electrolyte (EDF) can stably cycle 5000 times, and the capacity retention rate after the cycle is as high as 91.86%, and the average coulombic efficiency reaches 99.97%.
[0074] Furthermore, the specific capacity and coulombic efficiency of NFPP||Na batteries with Baseline and BEN electrolyte systems were tested at 55°C, 4V high voltage and 0.5C discharge rate. The results are as follows: Figure 2 As shown in (a) of Figure 2 (b) and (c) show the charge and discharge curves of NFPP||Na batteries assembled with two electrolyte systems.
[0075] from Figure 2 (a) and Figure 2 As can be seen from (b) in the figure, the NFPP||Na battery using the Baseline electrolyte was overcharged after 470 cycles, causing the battery to short-circuit. Figure 2 (a) and Figure 2 As can be seen from (c), the NFPP||Na battery using BEN electrolyte still has good cycle stability under high temperature conditions of 55°C, and the capacity retention rate is as high as 88.23% after 2000 cycles.
[0076] Furthermore, the specific capacity and coulombic efficiency of the NFPP||Na battery with ED and EDM electrolyte systems were tested at -20°C, 4V high voltage and 0.5C discharge rate. Figure 3 shown.
[0077] from Figure 3 It can be seen that under the extreme condition of -20℃, the capacity retention rate of the NFPP||Na battery using EDM electrolyte is as high as 100% after 400 cycles, with almost no capacity attenuation. At the same time, the average coulombic efficiency reaches 99.95%, showing excellent cycle stability, which is significantly better than the NFPP||Na battery using ED electrolyte.
[0078] At 25℃ and 4V high voltage, the specific capacity of NFPP||Na battery with PF and PFM electrolyte system was tested respectively. The results are as follows Figure 4 And as shown in Table 1.
[0079] Table 1 Electrochemical performance of NFPP||Na battery in different electrolytes
[0080]
[0081]
[0082] from Figure 4 It can be seen from the data in Table 1 that the discharge specific capacity of the PF battery at different rates is lower than that of the PFM electrolyte battery, and the PFM electrolyte system still has a considerable specific capacity at the ultra-high rate of 100C, while the PF electrolyte system can no longer release a high specific capacity at the high rate of 100C, which fully proves that the NFPP||Na battery assembled with compound 28 as an electrolyte additive has good rate performance.
[0083] At 25°C, 4V high voltage and 20C discharge rate, the specific capacity of NFPP||Na battery with NPF and NPFM electrolyte system was tested respectively. The results are as follows Figure 5 shown.
[0084] from Figure 5 It can be seen that the battery with NPFM electrolyte can stably cycle 10,000 times, with a capacity retention rate of 74.1% and an average coulombic efficiency of 99.81%. However, the specific capacity of the NPF battery is very low after 6,000 cycles. This shows that the NPFM system still exhibits excellent cycle stability at high rates.
[0085] Under the conditions of 3.65V voltage and 1C discharge rate, the specific capacity and coulombic efficiency of NFPP||HC sodium ion soft pack battery with TEMS electrolyte system were tested. The results are as follows Figure 6 shown.
[0086] from Figure 6 It can be seen that under the conditions of voltage 3.65V and rate 1C, the NFPP||HC soft-pack battery with TEMS electrolyte exhibits excellent cycle stability, and still has a capacity retention rate of 81.57% after 500 cycles, indicating that the BEN electrolyte improves the interface conditions and reduces the side reactions of the positive and negative electrodes, thereby enabling rapid ion conduction and giving it good electrochemical properties.
[0087] In summary, the phenyl group in the benzene sulfonate electrolyte additive of the present invention improves the anti-overcharge performance, and the sulfonate group can form a stable inorganic SEI film and improve the oxidation stability. Using it as an additive in the sodium ion battery electrolyte can not only effectively improve the battery's high voltage resistance, operating temperature range, safety, and cycle stability, but also is conducive to the promotion and application of low-cost, high-safety and long-cycle sodium ion secondary batteries in the field of energy storage, and solves the many performance shortcomings of existing sodium ion secondary battery electrolytes.
[0088] The technical solution of the present invention is not limited to the above-mentioned specific embodiments. All technical variations made according to the technical solution of the present invention fall within the protection scope of the present invention.
Claims
1. A benzenesulfonate additive, characterized in that: It is a compound of the structural formula shown in formula (I): Wherein: R1, R2, R3, R4 and R5 are one of hydrogen atoms, fluorine atoms, fluorinated alkanes or fluorinated ether groups having 1 to 3 carbon atoms; R6 is one of an alkane having 1 to 5 carbon atoms, a fluorinated alkane, a cyanated alkane and a silane group.
2. The benzenesulfonate additive according to claim 1, characterized in that: R1, R2, R3, R4 and R5 are one of the following groups: R6 is one of the following groups:
3. The benzenesulfonate additive according to claim 1 or 2, characterized in that: It is one of the following compounds 1 to 52:
4. Use of the benzenesulfonate additive as claimed in claim 2 or 3 in sodium ion battery electrolyte.
5. The use of the benzenesulfonate additive in sodium ion battery electrolyte according to claim 4, characterized in that: The sodium ion battery electrolyte is added with a benzene sulfonate additive having a volume fraction of 0.1% to 10%.
Citation Information
Patent Citations
Lithium secondary battery and electrolyte thereof
CN107799821A
Electrolyte additive for lithium secondary battery, and non-aqueous electrolyte and lithium secondary battery which comprise same
CN114041228A
Sodium-ion battery electrolyte as well as preparation method and application thereof
CN116315094A
Electrolytic solution for lithium secondary cell and lithium cell containing same
CN1385919A